Hubungan Motivasi dan Kepatuhan Penilaian Risiko Jatuh dengan Kejadian Jatuh di Ruang Rawat Inap Anak RS QIM Batang - Khairun Nisak; Nopi Nur Khasanah; Kurnia Wijayanti (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Patient safety is one of the main components in determining the quality of hospital services. Every hospital is required to minimize incidents that may harm patients. Among various patient safety incidents, falls in children rank second after medication errors, making them a serious issue that requires attention. This study aims to evaluate the relationship between nurses’ motivation and compliance in conducting fall risk assessments with the incidence of falls among pediatric patients in the inpatient ward of QIM Hospital Batang. This study employed a descriptive quantitative design with a correlational approach. A total of 44 nurses who met the inclusion criteria were recruited as respondents. Research instruments included a motivation questionnaire, an observation sheet on compliance, and records of patient fall incidents. Data were analyzed using the Spearman Rank test to measure the strength of the relationship between variables. The findings showed that most respondents (84.1%) had a high level of motivation, and all nurses (100%) demonstrated full compliance in performing fall risk assessments according to standard operating procedures. During the study period, no cases of pediatric falls were reported in the inpatient ward, indicating the effectiveness of fall risk assessment implementation. Statistical analysis produced a p-value of 0.011, indicating a significant relationship between motivation and nurses’ compliance. These findings emphasize that work motivation plays an important role in maintaining nurses’ consistency in adhering to safety procedures. Motivation can be enhanced through managerial support, continuous training, and the establishment of a strong patient safety culture, thereby reducing the risk of falls and improving the overall quality of healthcare services.